Investigation of the Molecular Mechanism of Coagulopathy in Severe and Critical Patients With COVID-19 - Elieh Ali Komi, Daniel; Rahimi, Yaghoub; Asghari, Rahim; Jafari, Reza; Rasouli, Javad; Mohebalizadeh, Mehdi; Abbasi, Ata; Nejadrahim, Rahim; Rezazadeh, Farzin; Shafiei-Irannejad, Vahid (Frontiers in Immunology, 2021)
Coagulopathy is a frequently reported finding in the pathology of coronavirus disease 2019 (COVID-19); however, the molecular mechanism, the involved coagulation factors, and the role of regulatory proteins in homeostasis are not fully investigated. We explored the dynamic changes of nine coagulation tests in patients and controls to propose a molecular mechanism for COVID-19-associated coagulopathy. Coagulation tests including prothrombin time (PT), partial thromboplastin time (PTT), fibrinogen (FIB), lupus anticoagulant (LAC), proteins C and S, antithrombin III (ATIII), D-dimer, and fibrin degradation products (FDPs) were performed on plasma collected from 105 individuals (35 critical patients, 35 severe patients, and 35 healthy controls). There was a statically significant difference when the results of the critical (CRT) and/or severe (SVR) group for the following tests were compared to the control (CRL) group: PTCRT (15.014) and PTSVR (13.846) (PTCRL = 13.383, p < 0.001), PTTCRT (42.923) and PTTSVR (37.8) (PTTCRL = 36.494, p < 0.001), LACCRT (49.414) and LACSVR (47.046) (LACCRL = 40.763, p < 0.001), FIBCRT (537.66) and FIBSVR (480.29) (FIBCRL = 283.57, p < 0.001), ProCCRT (85.57%) and ProCSVR (99.34%) (ProCCRL = 94.31%, p = 0.04), ProSCRT (62.91%) and ProSSVR (65.06%) (ProSCRL = 75.03%, p < 0.001), D-dimer (p < 0.0001, χ2 = 34.812), and FDP (p < 0.002, χ2 = 15.205). No significant association was found in the ATIII results in groups (ATIIICRT = 95.71% and ATIIISVR = 99.63%; ATIIICRL = 98.74%, p = 0.321). D-dimer, FIB, PT, PTT, LAC, protein S, FDP, and protein C (ordered according to p-values) have significance in the prognosis of patients. Disruptions in homeostasis in protein C (and S), VIII/VIIIa and V/Va axes, probably play a role in COVID-19-associated coagulopathy.